Vias de administração e fontes de ferro para leitões na maternidade - Clarice Speridião Silva Neta (2019)
Iron supplementation in swine production is substantial for the adequate supply of this mineral due to of the limited reserves of iron in piglets, in order to minimize the effects caused by iron deficiency anemia in the period of lactation. The main theme of this study is to compare different sources of iron under oral of administration to replace the injectable form from evaluations on performance and blood parameters of piglets in lactation and nursery. In Chapter 1 is described in the literature review which discusses the importance of the mineral supply form and the influence exerted in developing iron deficiency anemia in piglets. The experiment 1, described in Chapter 2, evaluated the effects of supplementation of different iron sources on performance and blood parameters of piglets. The evaluation was carried out during the stage of lactation with individual weights and blood samples to the 7, 14 and 21 days of age. It can be inferred that iron supplementation wielded effect on the performance of piglets so that oral supplementation was sufficient to maintain normal levels of blood parameters evaluated. In experiment 2, described in Chapter 3, was evaluated the physiological status of the iron from the iron dextran injectable and oral ferrous fumarate by assessing performance and blood parameters of piglets in lactation and nursery. The evaluation was performed during 21 days in the lactation ward from individual weighing of piglets in 1st and 21st day and blood collection during this period. In addition, was evaluated the iron concentration in faeces and mortality in the period of lactation. In the nursery, the animals were identified and weighed to 23 and 63 days old. Iron supplementation exercised effect on performance in the periods studied. However, the dynamics of iron was influenced by the use of iron dextran oral which provides satisfactory results in blood parameters. No mortality occurred in function of the sources used during lactation.